Presidentas municipales en México: acoso y violencia política (2010-2016) - Barrera Bassols, Dalia; Cárdenas Acosta, Georgina (Pontificia Universidad Católica del Perú, 2016)
This article presents the results of an investigation concerning political harassment and violence towards female mayors in Mexico. It also aims to paint a picture of the social and political background of these phenomena in the context of authoritarian, clientelistic and male chauvinistic politics, which is told through the testimonies of female mayors collected from 1996 until 2009. Violence against mayors of both genders in Mexico starts with the so called war on drugs –a policy adopted in 2006 by the Federal government- which generates denouncements and proposals from political parties and municipalist associations, as well as manifestations of worry of deputies and senators. The climate of generalized violence in the country reached a critical state in January of 2016 with the assassination of the mayor of Temixco –in the state ofMorelos-Gisela Mota Ocampo, the first female mayor to be assasssinated by an armed comando.The present article synthesizes the results of an hemerographic tracing while presenting some of the most representative cases of political harassment and violence against female mayors in Mexico from 2010 until January of 2016, when said assassination took place.

El artículo presenta resultados de una investigación en torno al acoso y la violencia política hacia las presidentas municipales en México. A través de testimonios y experiencias de las presidentas municipales, recabados entre 1996 y 2009, dibuja los antecedentes de los fenómenos mencionados, en el contexto de una cultura política autoritaria, clientelar y machista. Así, se presenta un panorama de la violencia política dirigida a los alcaldes y otros funcionariosmunicipales, que se desata a partir de la llamada guerra contra el narcotráfico (política adoptada por el Estado mexicano en 2006). Esta situación generó denuncias y propuestas de los partidos políticos y las asociaciones municipalistas, así como algunas manifestaciones de preocupación de algunos diputados y senadores. La violencia generalizada alcanza dimensiones críticas, incluyendo la dirigida hacia las mujeres en diversos espacios sociales. En enero de 2016, se llegó a un punto de quiebre con el asesinato de Gisela Mota Ocampo, alcaldesa de Temixco, Morelos, primera presidenta municipal en funciones asesinada por un comando armado. El artículo sintetiza los resultados de un seguimiento hemerográfico, presentando algunos de los casos más representativos de acoso y violencia política hacia las presidentas municipales en nuestro país de 2010 a 2016, finalizando con el caso de Gisela Mota Ocampo.
Municipal presidents in Mexico: Harassment and Political Violence (2010- 2016)
Keywords: Female Mayors; Political Violence; Municipalities; Alcaldesas; Violencia Política; Municipios; https://purl.org/pe-repo/ocde/ford#5.06.00